EFL STUDENTS’ VOICES ON NATIVE SPEAKER PRESENTERS ON YOUTUBE VIDEOS AND THEIR IMPACT ON STUDENTS’ ENGLISH COMPETENCY DEVELOPMENT - Wenda Marlin Kakerissa (EDU SCIENCES JOURNAL, 2023)
There have been many studies on YouTube and its advantages for learning English, yet a specific research on students’ perception of native speaker presenters is still rare. This study aimed to investigate students’ general perspectives on YouTube videos, and exploring students’ perspectives on YouTube video presenters/hosts (native speaker and non-native speaker), and how they positively affect students’ English competency. A descriptive analysis method was done by distributing a questionnaire written in Indonesian via Google form to 156 respondents. The result of questionnaire was then analysed qualitatively using Jeffreys’s Amazing Statistics Program (JASP) 0.14.1. A semi-structured interview to ten respondents to dig out more about their response for certain items or questions was also done. The analysis revealed that YouTube provides a wide variety of topics, available in multiple languages, and might be downloaded anytime. When the presenters are the native ones, the respondents got some positive impacts in improving their English competency. Students felt challenged in building their understanding of the content, could practice their listening skill correctly, may train and improve their speaking skill, got new English vocabulary, learn to pause, stress, and use appropriate intonations in uttering words, sentences, and phrases, could practice proper use of grammar, identify people’s live and behave, increase students’ general knowledge, increase their knowledge of English language culture, and they become more creative. However, some respondents preferred the non-native hosts since they tend to speak slower and sometimes switch to Indonesian that facilitates the respondents understanding.